2015
DOI: 10.1186/s12989-016-0143-7
|View full text |Cite
|
Sign up to set email alerts
|

Increase in oxidative stress levels following welding fume inhalation: a controlled human exposure study

Abstract: BackgroundTungsten inert gas (TIG) welding represents one of the most widely used metal joining processes in industry. It has been shown to generate a large majority of particles at the nanoscale and to have low mass emission rates when compared to other types of welding. Despite evidence that TIG fume particles may produce reactive oxygen species (ROS), limited data is available for the time course changes of particle-associated oxidative stress in exposed TIG welders.MethodsTwenty non-smoking male welding ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 61 publications
4
37
0
Order By: Relevance
“…However, we still observed significant increases in levels of urinary 8-OHdG and 8-iso-PGF2α in welding and office workers post-exposure. Our observations are consistent with previous findings in a control human exposure study 23 . Furthermore, we found that a 10-μg/m 3 increase in the mean PM 2.5 resulted in a 2.15% increase in 8-OHdG/uCr and a 8.43% increase in 8-iso-PGF2α/uCr in welding workers.…”
Section: Discussionsupporting
confidence: 93%
“…However, we still observed significant increases in levels of urinary 8-OHdG and 8-iso-PGF2α in welding and office workers post-exposure. Our observations are consistent with previous findings in a control human exposure study 23 . Furthermore, we found that a 10-μg/m 3 increase in the mean PM 2.5 resulted in a 2.15% increase in 8-OHdG/uCr and a 8.43% increase in 8-iso-PGF2α/uCr in welding workers.…”
Section: Discussionsupporting
confidence: 93%
“…Although toxicological evidence regarding cardiovascular disease is sparse, in vivo studies suggest tungsten causes histological lesions in the heart [115] and can inactivate molybdenum-enzymes by replacing molybdenum binding sites [116]. Tungsten likely causes oxidative stress [7, 11, 112, 117] and can modify cobalt toxicity [118]. There is little epidemiological evidence of tungsten exposure and cardiovascular disease in the general population, although tungsten exposure has been associated with elevated blood pressure [119], excretion of reactive oxygen species [117], and DNA methylation and hydroxymethylation [120].…”
Section: Current Perspectives and Resultsmentioning
confidence: 99%
“…Welders who were exposed to aluminum TIG WFs for 60 minutes showed a 45% increase in urinary 8-OHdG and a 14% increase in plasma 8-OHdG after 3 h, which is a pre-mutagenic DNA adduct implicated in carcinogenesis. An exposure-response relationship was found between particle number concentration in WFs and plasma 8-OHdG concentration [67,68]. Acute and chronic exposures to particulate matter 2.5 (PM 2.5 ) generated from welding activities was associated with a modest change in DNA methylation of the inducible nitric oxide synthases (iNOS) gene.…”
Section: Human Studiesmentioning
confidence: 99%